Investigation of Mechanical Properties of Jute Fiber Epoxy Reinforced by Synthesized Hematite (Fe2O3) Nanoparticles - Bhuiya, Anwarul Kabir; Reza, Sumon; Matin, Abdul; Islam, Ashadul; Gofur, A.; Mahmud, Abu; Hoque, Asadul (Journal of Composites and Biodegradable Polymers, 2019)
Jute fiber was modified by epoxy resin and hematite nanoparticle. In this study alpha Fe2O3 nanoparticle in size at 22~23 nm made of sol-gel method commonly known as hematite was used. Chopped and scoured jute fibre was washed, neutralized and finally dried called modified fiber. Modified fiber was grafted with admixture of polyethylene glycol and aluminum salt and grafted sheet was then cut into small pieces. The raw jute fiber was layered using epoxy and pressed preparing Raw Jute Reinforced Epoxy Composite (RJREC). Similarly, the Bleached Jute Reinforced Epoxy Composites (BJREC) and Modified Jute Reinforced Epoxy Composites (BJREC) were also prepared. The Modified Jute Fibre Nano Disperse Epoxy Composites (MJRNDEC) was prepared by sandwiching three layers of Modified jute fabric with epoxy and nano particle. Epoxy sheet with nanoparticles and without nanoparticle were also produced. Produced samples were characterized and compared Tensile in terms of their mechanical properties. Obtained results show that modified jute fiber epoxy nano Fe2O3¬ dispersed composites exert better tensile and flexural strength compared to raw and bleached jute fiber epoxy composites.